Analisis Legalitas Pemusnahan Barang Bukti Narkotika Dalam Proses Penegakan Hukum Tindak Pidana Narkotika Yang Belum Di Putus Oleh Pengadilan (Studi Putusan Perkara Nomor : 409/Pid.Sus/2021/Pn.Tjk) - Putri, Kenny Ayu; Astuti, Priscilla Eka; Sabekti, Maulana (CV. ITTC INDONESIA, 2022)
Introductioan: As the number and variety of crimes in Indonesia increases, so does the number and variety of cases handled by law enforcement officials related to crimes in the field of Narcotics, with different operating models being carried out to ensure that there are different types of evidence. confiscated from the perpetrators of the crime. or perpetrators of criminal acts who are legally processed further, in the article destroyed, by law enforcement and prosecution. Purposes of the Research: The purpose of this study is to analyze the legality of destroying evidence of Narcotics in the law enforcement process that has not been decided by the court. Methods of the Research: This research method uses primary data and secondary data in addition to normative and empirical juridical approaches. Results / Findings / Novelty of the Research: Article 45 of the Criminal Procedure Code, Articles 91 and 92 of Law Number 35 of 2009 concerning Narcotics, Article 26 of Government Regulation Number 40 of 2013, and Article 8 of Perkap Number 8 of 2014 concerning Amendments to Perkap Number 10 of 2010 concerning Events All of these factors contribute to the destruction Narcotics evidence. After being arrested and taken prisoner, sealed, confiscated, and destroyed, the evidence is then stored.